The Aquaculture Planning Simulator (APS) - Pedini M.; Coppola S.R.; Moretti A. (Aspects économiques de la production aquacole, 1995)
This paper describes the Aquaculture Planning Simulator (APS) module of the two aquaculture information systems of FAO, SIPAM and SIPAL. The APS, developed using the Borland dBase IV, is the analytical tool of the two aquaculture information systems for evaluation of project proposals through a comparison of both technical and economic parameters against similar projects already in operation and whose data are included in the data entry of the APS module. The design characteristics of the module are explained, and a brief indication of how the first release of the module works is also provided. The APS design allows both a technical and a financial tuning of the project proposals and is intended for use by the private sector, banking institutions, and government offices responsible for aquaculture development.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)